Análise da Revisão Cochrane: Pregabalina no Tratamento da Dor Crónica Moderada a Grave em Adultos com Fibromialgia. Cochrane Database Syst Rev. 2016;9:CD011790 e 2016;4:CD009002 - Ferreira-dos-Santos, G (2018)
Fibromyalgia can be clinically defined by widespread pain lasting for longer than 3 months with tenderness on palpation in 11 or more of 18 specified tender points. Many people with fibromyalgia are significantly disabled, and experience moderate to severe pain for many years, for which conventional analgesics are usually not effective. For these patients treatment options generally include antidepressants like tricyclic agents, serotonin and noradrenaline reuptake inhibitors, or anticonvulsants like pregabalin or gabapentin. Pregabalin is a drug licensed for the treatment of fibromyalgia in the United States of America, with a mechanism of action similar to gabapentin. This mode of action confers antiepileptic, analgesic, and anxiolytic effects. This Cochrane systematic review included 8 randomized, placebo-controlled trials with low risk of bias, which studied the effect of a daily dose of pregabalin for the treatment of moderate to severe pain in adult patients suffering from fibromyalgia. Of the main results of this systematic review we highlight the major effect that a daily dose of 300 to 600 mg of pregabalin had in the reduction of pain intensity over a follow-up period of 12 to 26 weeks, with tolerable adverse effects, for a minority of people with moderate to severe pain due to fibromyalgia. This paper aims to summarize and discuss the main results and conclusions of this systematic review, as well as its implications for the daily clinical practice.